PENGEMBANGAN MANAJEMEN DAYA TARIK WISATA BERBASIS QUALITY EXPERIENCES DI OBJEK WISATA ALAS KEDATON TABANAN - Yayu Indrawati; I P. Sudana; N P. Eka Mahadewi; IG.B. Sastrawan Mananda; N M. Ariani (Buletin Udayana Mengabdi, 2013)
In the recent days, to understanding the consumers behaviour is becoming a primary concern in marketing.This is also including in tourism marketing particularly tourism destination. The phenomenon of understandingthe consumer taste in tourism is popularly known as quality experience. It has a meaning that when tourist spendstheir money on a certain destination they expect for quality experience. It can be seen on their satisfaction thatappear on their willingness to revisit or giving the positive impression to their friends and relatives. Today, thereis a downward point in tourist destination in the last five years. Previously there were 1500 visitors per day, butlately it is only 10.000 both for international and domestic visitors. It is caused by the raise of competitor’s numberand the tourist responses towards Alas Kedaton site. Such impression comes from its cleanliness, the hospitalityof the staff, the price of entrance fee, and lack of facilities. Other instances are the uncomfortable way to get tothe site, as well as the absence of spiritual facilities for Muslim visitors for praying during their visit to this place.